Populasi Sonokeling (Dalbergia latifolia Roxb) di Cagar Alam Gunung Jagat Sumedang - Wilujeng, Sri; Fahmi Solihat, Raizal; Darliana, Ina (Rekayasa, 2025)
Rosewood (Dalbergia latifolia Roxb.) is a tree species with high economic value. The latest data on the global rosewood population was reported in 2020 to be in a vulnerable state of extinction, due to exploitation and regeneration constraints. The initial step in analyzing to restore and manage the existence of a tree species in an area is to observe the population density, population distribution patterns and determine associated plants. The sampling technique was carried out by determining a quadrant of 20 m x 20 m with 37 sampling units. The average density parameters of rosewood per plot were analyzed descriptively, the distribution pattern of rosewood populations was analyzed using the Standardized Morisita Index and the determination of the type of association between rosewood and other species was obtained through the Chi-square Test and Percent Co Occurrence. The results showed that there was a decrease in rosewood density per plot from the seedling level to the tree level. The sharpest decline occurred at the seedling level to the sapling level. The analysis of the rosewood distribution pattern showed a clumped pattern with a Standardized Morisita Index of 0.628. Analysis of rosewood association type, showed that 34 tree species were not associated with rosewood, negatively associated with Orophea hexandra (Blume) and positively associated with Swietenia macrophylla King. Between rosewood and 9 other species has percent Co Occurrence = 0, which shows that there is no interdependence between rosewood and other species. This finding is an important basis for conservation and habitat management efforts, with a focus on the regenerative phase and interspecies relationships to support the sustainability of rosewood populations.